The SOSIALISASI TENTANG PERILAKU BULLYING PADA SISWA MI MIFTAHUL HUDA I DESA SAMBIMULYO KECAMATAN BANGOREJO BANYUWANGI SEBAGAI UPAYA PENCEGAHAN TERJADINYA TINDAKAN BULLYING DI SEKOLAH - MS, Anis Hidayati (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2023)
The school which should be the comfortable place for students to gain the knowledge and develop their potential has changed into the zone of bullying practice. Because a lot of bullying cases happened at school, it is necessarily to do preventive action so that the cases do not increase. Therefore, we need to educate students about bullying earlier by conducting counseling about bullying in MI Miftahul Huda I, Sambimulyo Village, Bangorejo District, Banyuwangi City, because it is found that there are some bullying cases there. The method used in this study is divided into three stages, the first is preparation, the second is execution, and the third is evaluation. In this agenda, students are given knowledge about the definition, types, effects of bullying for the victims or the perpetrators, constitution/law towards the perpetrators, and followed by question and answer session and sharing thoughts. Then, the students are given animation film for the sake of giving examples of bullying in school life, and followed by evaluation. By conducting this agenda, students obtained a good training about the danger of bullying practice for students. It is proven by the rise of students’ understanding about issues delivered and discussed during the discussion and question and answer session. The suggestion given for students attending the agenda is to love and take care of their friends, either at school or outside of school. If they find bullying practice, they can handle it in a right way. If bullying happens at school, the school principal must be able to act decisively against perpetrators.